Incorporation of (U-14C)-glucose into glycogen in normal rat pancreatic islets (Revista Española de Fisiología, 1984)
The incorporation of glucose into glycogen was determined in pancreatic islets isolated from normal rats and incubated with glucose (5 or 20 mM) and compounds known to affect glycogen metabolism in other tissues.Incubation of pancreatic islets with glucose (20 mM) induced a marked increase in radioactive glycogen.Exposure to epinephrine in the presence of glucose (20 mM) slightly increased incorporation of glucose into glycogen.In contrast the incorporation of glucose into glycogen was not affected when isolated islets were exposed to glucagon or insulin, whereas anti-insulin serum in the incubation medium decreased radioactive glycogen formation.